2009
DOI: 10.2337/dc09-1327
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Interactive Diary: A New Telemedicine System Enabling Flexible Diet and Insulin Therapy While Improving Quality of Life

Abstract: OBJECTIVEWidespread use of carbohydrate counting is limited by its complex education. In this study we compared a Diabetes Interactive Diary (DID) with standard carbohydrate counting in terms of metabolic and weight control, time required for education, quality of life, and treatment satisfaction.RESEARCH DESIGN AND METHODSAdults with type 1 diabetes were randomly assigned to DID (group A, n = 67) or standard education (group B, n = 63) and followed for 6 months. A subgroup also completed the SF-36 Health Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
185
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(190 citation statements)
references
References 16 publications
2
185
0
3
Order By: Relevance
“…Moreover, the question remains as to who will be responsible for covering the attributable costs of this innovation in the real world. Unfortunately, only three studies 24,28,30 in this review had cost/benefit analysis information, in which they reported that selfmonitoring and management of diabetes via mobile phone technology would be cost-effective at approximately €4/month, 2 pence/text, and €1.4/month respectively. Nevertheless, the applicability of mobile technology in low resources settings is still questionable in terms of its overall cost (phone, internet and operation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the question remains as to who will be responsible for covering the attributable costs of this innovation in the real world. Unfortunately, only three studies 24,28,30 in this review had cost/benefit analysis information, in which they reported that selfmonitoring and management of diabetes via mobile phone technology would be cost-effective at approximately €4/month, 2 pence/text, and €1.4/month respectively. Nevertheless, the applicability of mobile technology in low resources settings is still questionable in terms of its overall cost (phone, internet and operation).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum difference reported at the end of the study period in the intervention group was -0.1 (6.4% pretest to 6.3% at 3 months) while the maximum difference was -2.4 (9.8% pretest to 7.4% at 3 months). Ten studies showed lower HbA1c levels among participants in the intervention group at the end of the intervention, although only seven 17,19,20,25,27,28,30 reported significant reduction in HbA1c levels (p < 0.05). Meta-analysis suggests that during an average followup of 6.3 years, an overall net effect of HbA1c reduction of the 12 studies in intervention groups was 0.39% (95%CI: -0.067, -0.72, p=0.018) after taking off the reduction in control groups.…”
Section: Effects Of Interventionmentioning
confidence: 98%
See 1 more Smart Citation
“…Teaching patients about carbohydrate counting via a mobile phone has been shown to reduce hemoglobin A1c levels similar to that achieved by "traditional" structured patient education programs but requires significantly less health care provider resource. 28 In a meta-analysis assessing the impact of mobile phone interventions on glycemic control, Liang and colleagues 29 assessed 22 studies involving more than 1600 participants and reported that this type of intervention led to a reduction in hemoglobin A1c of the order of 0.5% and that mobile phone interventions are especially valuable for patients with type 2 diabetes.…”
Section: Self-monitoring Of Blood Glucose In the Future: The Role Of mentioning
confidence: 99%
“…There are existing mobile feedback solutions for diabetes patients, such as the DID by Rossi et al [6], yet they are not platform based and thus isolated solutions. METABO is meant to be much more integrative.…”
Section: Introductionmentioning
confidence: 99%